Cost-effectiveness analysis of Belimumab in patients with systemic lupus erythematosus in Spain - Silvia Díaz-Cerezo; Ángel María García-Aparicio; Javier Parrondo; Laura Amanda Vallejo-Aparicio (Elsevier, 2015)
Objective: To estimate the cost-effectiveness of belimumab in patients with systemic lupus erythematosus (SLE) presenting positive biomarkers and active disease despite standard treatment (ST), from the Spanish social perspective. Methods: A microsimulation model was used to estimate the cost-effectiveness of belimumab plus ST versus ST alone. A treatment duration of two years with a life-time horizon were considered. Efficacy data were obtained from belimumab clinical trials and the evolution of the disease was simulated from John Hopkins ´patient cohort data in the United States. Utility data were obtained from literature review. Direct and indirect costs were calculated based on Spanish published data (€, 2014), applying a discount rate (DR) of 3% to both costs and effects. Results were expressed as incremental cost-effectiveness ratio (ICER) in terms of gained life years (LY) and quality of life adjusted life years (QALYs). Probabilistic (PSA) and deterministic sensitivity analyses (DR of 0% and 5%, 5-years treatment duration and excluding indirect costs) were performed to determine the robustness of the model. Results: The incremental cost-effectiveness ratio (ICER) was 16,647€ per life year gained, with an incremental cost-utility ratio (ICUR) of 23,158€ per additional QALY gained. In 68% of the scenarios simulated in the PSA, belimumab was found to be a cost-effective alternative, considering a threshold of 30,000€/ QALY. Conclusion: Belimumab can be regarded as a cost-effective alternative from the Spanish social perspective